Brocas brain - "Sagan ,Carl" (London, 1979)
(3z(BMagnificent . . . Delightful . . . A masterpiece. A message of tremendous hope for humanity . . . While ever conscious that human folly can terminate man$1 (Bs march into the future, Sagan nonetheless paints for us a mind-boggling future: intelligent robots, the discovery of extraterrestrial life and its consequences, and above all the challenge and pursuit of the mystery of the universe.(3ys
Keywords: Psychology